Long Term Anticoagulation (4–16 Years) Stops Progression of Idiopathic Hip Osteonecrosis Associated with Familial Thrombophilia - Charles J. Glueck; Richard A. Freiberg; Robert Wissman; Ping Wang (Advances in Orthopedics)
In 6 patients with familial thrombophilia (5 Factor V (FV) Leiden heterozygotes, 1 with resistance to activated protein C (RAPC)), we prospectively assessed whether continuous longterm (4–16 years) anticoagulation would prevent progression of idiopathic osteonecrosis (ON), ameliorate pain, and facilitate functional recovery. Four men and 2 women (9 hips, 8 Ficat stage II, 1 stage I) were anticoagulated with enoxaparin (60 mg/day) for 3 months and subsequently with Coumadin, Xarelto, or Pradaxa, warranted by ≥2 prior thrombotic events. Anticoagulation was continued for 4, 4, 9, 13, 13, and 16 years, with serial clinical and X-ray follow-up. On 4–16-years anticoagulation, 9 hips in the 6 patients (8 originally Ficat II, 1 Ficat I) remained unchanged, contrasted to untreated ON Ficat stage II, where 50%–80% of hips progress to collapse (Ficat stages III-IV) within 2 years after diagnosis. Within 3, 3, 3, 9, and 16 months after starting anticoagulation, 5 patients became pain-free and remained asymptomatic throughout follow-up; the 6th patient required Percocet for pain. There were no significant bleeding episodes. Long term (4–16 years) anticoagulation initiated in Ficat stages I-II of idiopathic hip ON in patients with FV-RAPC changes the natural history of ON, stopping progression, resolving pain, and restoring function.